PELATIHAN PEMANFAATAN MEDIA WORDWALL UNTUK GURU DAN SISWA DI SDN CURAHMALANG III - HARTININGRUM, ESTY SARAWATI NUR; Boediono, Slamet; Rahman, Fatchiyah; Shokhifatul Lail, Tutik; Nur Fahmi, Vicky Mahendra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Jombang), 2024)
SDN CURAHMALANG III is one of the schools owned by the village of Kurahmalang with adifferent location, which is located at the corner of the rice fields and the border to Mojoagung, thereare 52 students from grades 1-6 with a limited number due to the small number of local residents. Thenumber of teachers is 12 teachers including the principal. The use of virtual media at SDNCurahmalang is still not maximized, so the purpose of this service is to provide training on one mediathat can help teachers to be able to use technology-based interactive media. The Wordwall applicationhelps teachers create a form of learning media, one of which is an interesting quiz, the matchmakingmethod. Word search etc. This application has many benefits, one of which can be downloaded andprinted so that it can be used as an attachment to learning devices. For students this application isinteresting so that students do not feel bored in learning, because students do not feel like doing quizzesbut like playing games. The method used is training and mentoring. The result of this service is thatthe teacher can create interactive media and students can operate the results of the wordwall mediathat has been made by the teacher. This wordwall media is suitable for elementary school studentsbecause the templates are diverse and attractive